The Transformation of Philanthropy in Public Spaces: From the Tradition of Street Charity to an Islamic Social Economy Movement - Masdar, Rita; Fahlefi, Rizal (El-kahfi | Journal of Islamic Economics, 2025)
This research examines the transformation of philanthropy in public spaces, shifting from the practice of street charity (sedekah jalanan) toward a sustainable Islamic social economy movement, utilizing a Systematic Literature Review (SLR) approach. Out of 120 initial articles screened, 14 valid articles were analyzed to identify current patterns, themes, and practices. The review reveals four main findings: (1) street philanthropy functions as social capital that strengthens community solidarity and religious values; (2) spontaneous charity can be transformed into productive philanthropy through instruments like Zakat or Waqf (endowment), fostering the economic independence of recipients; (3) integration with Islamic social economy institutions, such as mosques and cooperatives, enhances accountability and sustainability; and (4) digitalization expands the participation of the younger generation and improves fund distribution efficiency. This phenomenon asserts that street philanthropy is not merely an act of giving, but a strategic instrument for socio-economic development rooted in Islamic values. This study concludes that strengthening coordination, transparency, and the integration of spiritual values with productive mechanisms can turn street philanthropy into a modern Islamic social economy movement that is inclusive, effective, and sustainable. These findings offer practical and theoretical contributions to the development of Islamic social economy literature and community-based philanthropic practices.